Individual debt limitation of territorial self-government entities as either threat or opportunity in creating local development - Filipiak, Beata Zofia (Indywidualna limitacja zadłużenia jednostek samorządu terytorialnego szansą czy przeszkodą w kreowaniu rozwoju lokalnego, 2015)
Individual debt ratio limits the possibility of borrowing by local government units. The changes that occurred in 2014 will have an impact on the financing of current tasks, but primarily they affect the realization of investment projects, which are the basis of local development. The purpose of the paper is to present the results and limitations resulting from changing regulations concerning the possibility of incurring debt and also to present self-government entities’ opinion on the changes that the Public Finance Law is going to bring about. The study was conducted among self-government entities. The method that was used to gather the data was a questionnaire. A total of 397 questionnaires were obtained, which means that the answer was given by 397 local government units
Biblioteka Regionalisty, 2015, Nr 15, s. 19-32
Keywords: finance; territorial self-government finance; debt; individual debt ratio; local development; finanse; finanse samorządu terytorialnego; dług; indywidualny wskaźnik zadłużenia; rozwój lokalny